Analysis of the Driving Factors for Digital Newspaper Paid Subscription - Giannisa Umara; Triana Rahajeng Hadiprawoto (Green Publisher Indonesia, 2025)
The digital era has revolutionized access to information through digital news platforms, but attracting paid subscribers for digital newspaper remains a challenge for the media industry. The purpose of this study is to investigate the factors that influence customer satisfaction toward digital news platform and, subsequently, on digital newspaper paid subscription. The research employed a quantitative approach and partial least squared structural equation modelling to investigate the impact news site quality on consumer satisfaction and digital newspaper paid subscription. The data were collected through online questionnaires from 212 individuals who actively pays for subscription to a digital newspaper in digital news platform in Indonesia. The results of this study indicate that price point, flexible service, convenience, news quality, and commitment have a positive influence on customer satisfaction, and customer satisfaction positively affects customer loyalty towards digital newspaper paid subscription. These findings emphasize the importance of price, flexible service, convenience, news quality, commitment, customer satisfaction and their role in cultivating paid subscriptions towards digital newspaper. This study contributes to the existing literature on digital newspaper subscription by exploring the factors influencing consumer satisfaction in this context. The findings provide implications for digital newspaper companies to formulate strategies and policies in delivering their services, in order to increase paid subscribers and maintain their competitive position.